The VISCACHA survey - VII. Assembly history of the Magellanic Bridge and SMC Wing from star clusters - Oliveira, R. A. P. (2023)
The formation scenario of the Magellanic Bridge during an encounter between the Large and Small Magellanic Clouds ~200 Myr ago, as proposed by N-body models, would be imprinted in the chemical enrichment and kinematics of its stars and sites of ongoing star formation along its extension. We present an analysis of 33 Bridge star clusters using photometry obtained with the SOAR 4-m telescope equipped with adaptive optics for the VISCACHA survey. We performed a membership selection and derived self-consistent ages, metallicities, distances, and reddening values via statistical isochrone fitting, as well as tidal radii and integrated masses from structure analysis. Two groups are clearly detected: 13 well-studied clusters older than the Bridge, with 0.5-6.8 Gyr and [Fe/H]<−0.6 dex; and 15 clusters with <200 Myr and [Fe/H]>−0.5 dex, probably formed in situ. The old clusters follow the overall age and metallicity gradients of the SMC, whereas the younger ones are uniformly distributed along the Bridge. The main results are as follows: (i) we derive ages and metallicities for the first time for 9 and 18 clusters, respectively; (ii) we detect two metallicity dips in the age-metallicity relation of the Bridge at ~200 Myr and 1.5 Gyr ago for the first time, possibly chemical signatures of the formation of the Bridge and Magellanic Stream; (iii) we estimate a minimum stellar mass for the Bridge of 3-5 × 105 M⊙; (iv) we confirm that all the young Bridge clusters at RA<3h are metal-rich with [Fe/H]∼−0.4 dex.